Marketing communication strategy Sawah Pematang Johar tour in improving tourist visits - Sari, Venna Melinda; Anshori, Akhyar (COMMICAST, 2022)
Tourism objects are one of the business fields that are developing so fast and creating competition between one tourist attraction and another in reaching visitors or tourists. Tourist attractions are actively developing to improve existing tourist locations continuously and make updates related to marketing strategies. The purpose of this study was to determine the marketing communication strategy for Sawah Pematang Johar tourism to increase tourist visits. This study used the descriptive qualitative method. Data obtained from observation, interviews, and documentation using descriptive analysis techniques, which describe the events under study. In this study, the number of informants was 5 people, namely the owner of the rice fields, field officers, to tourists. The research location is in the tourism village of the Pematang johar rice field, Deli Serdang Regency. The results showed that in marketing, the village government used a communication strategy to attract tourists in three ways, namely promotion through social media in the form of Facebook, Instagram, YouTube, MU television broadcasts, and word of mouth. The second activity is a place in the form of a comfortable, beautiful, and natural place. The third activity Price is in the form of very affordable entrance ticket prices. The second activity is a place in the form of a comfortable, beautiful, and natural place. The third activity Price is in the form of very affordable entrance ticket prices. The second activity is a place in the form of a comfortable, beautiful, and natural place. The third activity Price is in the form of very affordable entrance ticket prices.